Sistema de indicadores para la sostenibilidad del sector turístico del cantón Portoviejo en el contexto del covid-19 - Loor Vera, Kevin Hernán (2022)
The objective of this work was to develop a system of sustainability indicators that contributes to the improvement of the tourism sector in Portoviejo canton in the context of COVID-19, the research that was developed was of an exploratory type with a mixed approach. To carry out this study, three phases were established: starting from the diagnosis, through a bibliographic - documentary review where important aspects such as geographical, environmental, economic, sociocultural and infrastructure characteristics were identified and delimited; the profile, tendency and satisfaction of the tourist was continuously evaluated through 196 virtually formalized surveys, in addition a SWOT analysis was carried out that, once weighted, determined the main variables to formulate the problem and strategic solution. Respectively, with the analysis it was possible to know that the canton presents certain intersectoral initiatives that are focused on the reactivation of tourism, for which, due to the conditions of the pandemic, it was carried out based on the triple helix model, resulting in 4 of the 5 in promotion by the municipal government. Second, through the evaluation of the 7 experts, it was possible to validate the sustainable indicators that are directed according to the importance and interaction of the fundamental pillars. Finally, each of them was described to associate them with the public, private and academic sectors; in turn, a varied comparison matrix was developed, managing to identify the level of importance and thus structure the hierarchical file to comply with sustainability actions.